Antimetastatic effects of Rheum palmatum L. extract on oral cancer cells. Issue 10 (5th July 2017) - Chen, Yang‐Yu; Hsieh, Ming‐Ju; Hsieh, Yih‐Shou; Chang, Yu‐Chao; Chen, Pei‐Ni; Yang, Shun‐Fa; Ho, Hsin‐Yu; Chou, Ying‐Erh; Lin, Chiao‐Wen
Abstract: Rheum palmatum L., a traditional Chinese medication, has been used for the treatment of various disorders. However, the detailed impacts and underlying mechanisms of R. palmatum L. extracts (RLEs) on human oral cancer cell metastasis are still unclear. Here, we tested the hypothesis that an RLE has antimetastatic effects on SCC‐9 and SAS human oral cancer cells. Gelatin zymography, Western blot, real‐time polymerase chain reaction, and luciferase assay were used to explore the underlying mechanisms involved in the antimetastatic effects on oral cancer cells. Our results revealed that the RLE (up to 20 μg/mL, without cytotoxicity) attenuated SCC‐9 and SAS cell motility, invasiveness, and migration by reducing matrix metalloproteinase (MMP)‐2 enzyme activities. Western blot analysis of the MAPK signaling pathway indicated that the RLE significantly decreased phosphorylated ERK1/2 levels but not p38 and JNK levels. In conclusion, RLEs exhibit antimetastatic activity against oral cancer cells through the transcriptional repression of MMP‐2 via the Erk1/2 signaling pathways. Thus, RLEs may be potentially useful as antimetastatic agents for oral cancer chemotherapy.